Architecture as a narrative of identity: the atemporal memory of space in contemporary dwelling - Ramos Cornejo, Renzo Roberto (2025)
Architecture, more than a material construction, constitutes a narrative that links memory and the present. This narrative character is timeless: from prehistoric shelters to contemporary cities, inhabited space has transmitted symbols, ways of life, and cultural traces. However, in the context of globalization and urban homogenization, this narrative faces the risk of being diluted. This article argues that architectural memory is not a vestige of the past but a living resource that accompanies humanity in every era and configures cultural identities through the appropriation of space. Architecture first appears as a signifier, but acquires meaning over time through the experience of its users, becoming a support of memory and identity. The hypothesis holds that every inhabited space embodies identity because every adaptation to the human condition leaves memory traces that transcend epochs and uses. The research is based on a hermeneutic and comparative analysis of theoretical texts and architectural case studies, with emphasis on examples from central and southern Peru, as well as dialogues with Latin American experiences and other international contexts. The results show that architecture, conceived as a narrative of identity, maintains a historical continuity that crosses styles and periods, and today offers keys to resist the loss of meaning in contemporary dwelling. The discussion emphasizes the need to recover this narrative dimension in the practice and teaching of architecture. It concludes that understanding architecture as a narrative of identity and a support of memory constitutes both a methodological tool and a cultural foundation for designing habitable spaces that do not forget their historical and collective roots.